Characterization of OCT3/4, Nestin, NANOG, CD44 and CD24 as stem cell markers in canine prostate cancer - Costa, Camila Dorotea [UNESP] (2019)
The cancer cell population is heterogeneous, and cancer stem cells (CSCs) are important for tumor growth and maintenance. The CSC population is associated with different neoplastic characteristics, such as cell migration, resistance to apoptosis, radiation therapy and chemotherapy. To increase the knowledge of CSCs in canine prostate cancer (PC), we characterized CSC markers in canine PC tissues and tumorspheres. We performed immunohistochemistry of OCT3/4, Nestin, NANOG, CD44 and CD24 in 10 normal canine prostatic tissue samples, 10 prostatic hyperplastic (PH) tissue samples and 28 PC tissue samples. Then, we established two canine prostate cancer cell cultures and characterized the CSC profile of tumorspheres grown from these cultures. Normal and PH tissues were positive for Nestin, NANOG, CD44 and CD24 only in the basal cell layer. OCT3/4 was expressed in the luminal cells of normal and PH tissues. There was no significant difference in Nestin expression among the prostatic tissues. However, we found higher expression of NANOG and CD44 in canine PC tissues than that in normal and PH tissues. Tumorspheres from canine prostate cancer cells express OCT3/4, Nestin, NANOG and CD44, indicating that these markers may be potential cancer stem cell markers in canine PC. The results obtained can be useful to better characterize the stem cell population in canine prostatic cancer and to guide future studies in comparative oncology.